Pengaruh Beban Kerja, Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Srijasa Brika Perkasa Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to test the hypothesis of the effect of workload, work stress and work motivation on employee performance. The population in this study were all employees at PT. Srijasa Brika Perkasa Palembang, totaling 37 people. The sampling technique in this study is a saturated sample because all the population is used as a sample, which is where all employees who work at PT. Srijasa Brika Perkasa Palembang, which amounted to 37 people, were used as samples. The data comes from the questionnaire data of employees of PT. Srijasa Brika Perkasa Palembang. The results of the data management hypothesis test obtained that the multiple linear regression equation for the variables of workload, work stress, and work motivation on employee performance was Y = -2.678 + 0.270 X1 + 0.584 X2 + 0.266 X3. Based on the t-test of the workload variable hypothesis, a significant value of 0.000